Is the association of subjective SES and self-rated health confounded by negative mood? An experimental approach - Kraus, Michael W; Adler, Nancy; Chen, Teh-Way David (Health psychology, 2013)
Lower subjective socioeconomic status (SSS) consistently shows associations with poorer health with the strongest relationships emerging with global self-rated health. Though often interpreted as reflecting the impact of low SSS on health, the association could also arise from confounding SSS with negative affect. In this research we sought to determine if negative affect confounds, or alternatively, is on the causal pathway linking SSS to self-rated health. Three-hundred adult participants--recruited from throughout the United States--were randomized to experience sadness, shame, or a neutral mood induction in which they wrote about and visualized a particularly emotionally evocative event. Participants subsequently completed measures of SSS, self-rated health, depression, and negative mood. Consistent with predictions, neither SSS scores nor the association of SSS with self-rated health, depression, and chronic negative affect differed by mood induction condition, controlling for demographic factors that covary with SSS (e.g., age, gender, education, income). Moreover, chronic negative affect partially explained the relationship between SSS and self-rated health, independent of manipulated mood. These findings support the utility of the measurement of SSS, and provide evidence suggesting that chronic negative affect is a likely mediator of the SSS association with global health rather than a confounder.